1997
DOI: 10.1046/j.1365-2141.1997.2783095.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing collection of peripheral blood progenitor cells following high‐dose cyclophosphamide and granulocyte colony‐stimulating factor in patients with multiple myeloma

Abstract: We treated 103 multiple myeloma (MM) patients with 7 g/m2 cyclophosphamide (Cy) followed by 300 μg G‐CSF/d to harvest peripheral blood progenitor cells (PBPC). PBPC autografts containing > 2.0 × 106 CD34+ cells per kg body weight were obtained at the first attempt from 90/100 evaluable patients. The most significant factor predicting impairment of PBPC collection was the duration of previous melphalan treatment (P < 0.0001). In multivariate discriminate analysis, treatment with melphalan during the most recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
152
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 21 publications
(29 reference statements)
13
152
2
Order By: Relevance
“…Thus, even if HGF could decrease the hematological toxicity of HDCYC, their use did not seem to change significantly this difference for the others. 29,32 As we observed, other parameters also involved in PBPC collection efficiency such as duration of therapy before HDCYC are important for HDCYC tolerance. Indeed, in a more recent study reporting results of total therapy, no death was observed after HDCYC 6 g/m 2 in newly diagnosed MM patients.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Thus, even if HGF could decrease the hematological toxicity of HDCYC, their use did not seem to change significantly this difference for the others. 29,32 As we observed, other parameters also involved in PBPC collection efficiency such as duration of therapy before HDCYC are important for HDCYC tolerance. Indeed, in a more recent study reporting results of total therapy, no death was observed after HDCYC 6 g/m 2 in newly diagnosed MM patients.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, comparative studies have reported that an increase in the CYC dose resulted in an increase in the number of PBPC harvested, irrespective of whether HGF were used or not. 28,29 In another study, patients treated with a lower dose of CYC had a less pronounced mobilization when compared with a high-dose CYC group. 30 Moreover, a significantly lower potentially malignant B cell content of autografts harvested after 7 g/m 2 is a further argument to prefer this dosage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…20,21,25 Novel antiangiogenic treatment approaches are currently investigated and might be used in MM in the near future. 26,27 In fact, the successful treatment of MM patients with thalidomide that has antiangiogenic effects was shown by Singhal et al 11 Preclinical models show that antiangiogenic treatment and tumor cell directed treatment approaches might have synergistic effects.…”
Section: Discussionmentioning
confidence: 99%